NEW INDICATIONS OF ULTRAHIGH-PRESSURE METAMORPHISM IN THE MICA SCHISTS OF THE KULET SITE OF THE KOKCHETAV MASSIF (NORTH KAZAKHSTAN) - Shatskii V.S.; Theunissen K.; Dobretsov N.L.; Sobolev N.Y. (My University, 1998)
The first finding of coesite in the garnet-mica schist of the Kulet site of the Kokchetav Massif is described. This fact indicates that the upper eclogite-bearing unit of the Kokchetav Massif was metamorphosed at pressures higher than 26 kbar. The estimated equilibrium temperatures for eclogites and garnet-amphibole-zoisitic and garnet-kyanite-biotite-amphibolic rocks show that the temperature of the high-pressure stage of metamorphism did not exceed 650°C. Taking into account that the rocks of the lower and upper tectonic units are characterized by the same metamorphism age, the authors conclude that the Zerenda series is a tectonic mixture of the combined fragments of the thin continental crust of a passive margin, subduced to different depths in the Lower Cambrian and rapidly (less than for a million years at the first stage) extracted to the level corresponding to the amphibolite facies of metamorphism. This may be indicated by the finding of kinetically unstable coesite in rocks differing in composition and metamorphism degree.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская